Transcription closed and open complex dynamics studies reveal balance between genetic determinants and co-factors. (19th May 2015) - Sala, Adrien; Shoaib, Muhammad; Anufrieva, Olga; Mutharasu, Gnanavel; Jahan Hoque, Rawnak; Yli-Harja, Olli; Kandhavelu, Meenakshisundaram
Abstract: In E. coli, promoter closed and open complexes are key steps in transcription initiation, where magnesium-dependent RNA polymerase catalyzes RNA synthesis. However, the exact mechanism of initiation remains to be fully elucidated. Here, using single mRNA detection and dual reporter studies, we show that increased intracellular magnesium concentration affects P lac initiation complex formation resulting in a highly dynamic process over the cell growth phases. Mg 2+ regulates transcription transition, which modulates bimodality of mRNA distribution in the exponential phase. We reveal that Mg 2+ regulates the size and frequency of the mRNA burst by changing the open complex duration. Moreover, increasing magnesium concentration leads to higher intrinsic and extrinsic noise in the exponential phase. RNAP-Mg 2+ interaction simulation reveals critical movements creating a shorter contact distance between aspartic acid residues and Nucleotide Triphosphate residues and increasing electrostatic charges in the active site. Our findings provide unique biophysical insights into the balanced mechanism of genetic determinants and magnesium ion in transcription initiation regulation during cell growth.